Restructuring Rural Health Care: Expanding the PACE for Rural Elders - Jeanette VanderMeer; Grant Savage; Jullet Davis (Rural Nurse Organization; Binghamton University, 2001)
The Balanced Budget Act (BBA) of 1997 created an opportunity for improving long-term care for the rural frail elderly by granting permanent provider status to the Program of All-Inclusive Care for Elders (PACE) under Medicare.  PACE is a unique managed care model that provides comprehensive, integrated acute and long-term services for frail elders and program providers assume full financial risk.  However, all existing PACE sites are currently located in urban settings.  This article reviews the PACE provisions in the BBA legislation and describes the current PACE model.  Two possible adaptations of the model are discussed for expanding PACE into rural areas. Keywords: Balanced Budget Act of 1997, long-term care, rural, frail elders, family caregivers, Program of All-Inclusive Care (PACE), Medicare restructuring http://dx.doi.org/10.14574/ojrnhc.v2i1.476